ELECTRIC AND ELASTIC PARAMETERS OF CARBONIC PERIOD TERRIGENOUS ROCKS OF THE EASTERN PART OF THE NORTHERN EDGE OF THE DNIEPER-DONETS DEPRESSION - Vyzhva, S.; Onyshchuk, V.; Orlyuk, М.; Onyshchuk, І.; Reva, М.; Shabatura, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main objective of this article is studying of electrical and acoustic parameters of Carbonic period terrigenous rocks of the eastern part of the northern edge of the Dnieper-Donets depression (DDD). It was determined that in atmospheric conditions the resistivity of dry extracted rocks (the specific electrical resistivity of framework of grains) varies from 6.522 km to 2.782 Mm (mean 1.033 Mm), for sandstones – from 16.18 km to 206.815 Mm (mean 27.973 Mm). The resistivity of rocks saturated with model of reservoir water (salinity M = 180 g/l) varies: for siltstones from 3.3 m to 26.8 m (mean 8.5 m), for sandstones from 2.9 m to 20.3 m (mean 8.2 m). In laboratory it was defined that in atmospheric conditions formation resistivity factor varies: for siltstones from 41.2 to 277.9 m (mean 96.2 m), for sandstones from 34 m to 238.5 m (mean 94.5 m). Physical modelling of reservoir conditions (temperature 94-126 С, confining stress 41-55 MPa, salinity M = 180 g/l) showed that the specific electrical resistivity varies: for siltstones from 0.4 m to 7.7 m (mean 2.1 m), and sandstones – from 0.4 m to 3.5 m (mean 1.3 m). Due to the closure of microcracks and the deformation of the pore space, the electrical resistance of rocks increases with increase of pressure. The regression dependence of the formation resistivity enlargement factor with pressure for the studied rocks manifest itself in second order polynomial. It was determined that in reservoir conditions the range of the formation resistivity factor varied: for siltstones from 132 to 2480 m (mean 562 m), for sandstones from 81 to 953 m (mean 339 m). Laboratory acoustic study of velocities of the P-waves in dry extracted rocks showed that this parameter varies: for siltstones from 2616 m/s to 4706 m/s (average 3940 m/s), for sandstones from 3660 m/s to 4971 m/s (average 4245 m/s). If rocks are saturated with model of reservoir water, velocities have higher values of P-waves: for siltstones from 3596 m/s to 5438 m/s (average 4681 m/s), for sandstones from 4302 m/s to 5463 m/s (average 4942 m/s). It was determined by physical modelling of reservoir conditions that velocities of P-waves vary: for siltstones from 3763 m/s to 6223 m/s (mean 5053 m/s), for sandstones from 4430 m/s to 5752 m/s (mean 5176 m/s). With the increase of pressure, the velocity of P-waves increases as well due to the closure of microcracks and the deformation of the pore space. The dependence of the increase in velocity from pressure is described by second order polynomial. The comprehensive analysis of electrical and acoustic parameters of condensed rocks has been resulted in a set of correlation ratios between reservoir, electric and elastic parameters of studied samples in normal and modeling conditions.
Keywords: siltstone; sandstone; electrical resistivity; formation resistivity factor; velocities of elastic waves